Prevalence of menopausal symptoms and their influence on adherence in women with breast cancer. (June 2014) - Kyvernitakis, I.; Ziller, V.; Hars, O.; Bauer, M.; Kalder, M.; Hadji, P.
Abstract Objectives The use of aromatase inhibitors for the adjuvant treatment of breast cancer may affect the quality of life of patients, as well as adherence to treatment. Methods Here we report the 2-year results of the 180 patients in the COMPAS study. This is the first randomized, controlled study reporting on menopausal symptoms under endocrine treatment with aromatase inhibitors in breast cancer patients, based on the Menopause Rating Scale. We analyzed the prevalence of menopausal symptoms as well as their associations with patient adherence. Results Baseline characteristics showed no significant differences among the control and the intervention groups. The majority of women experienced the symptoms at various severities. Overall, we found an increase in the prevalence of hot flushes, sleep disorders, bladder problems, dryness of the vagina as well as of joint and muscular discomfort between the 12- and 24-month visits. In compliant patients, all symptoms except for vaginal dryness improved between the 12- and 24-month visits while, in non-compliant women, hot flushes, irritability, dryness of the vagina as well as joint and muscular discomfort deteriorated. When comparing compliant and non-compliant patients, we found a significant difference only for anxiety (p = 0.028) in the 12-month analysis, as well as a large but non-significant difference for heart discomfort (p = 0.089) in the 24-month visit. Conclusions Our results indicate that the majority of women treated with aromatase inhibitors are experiencing menopausal symptoms at various severities. We showed that the mean symptom values in compliant patients improve with longer therapy duration. Furthermore, anxiety correlates with better compliance, while heart discomfort may lead to therapy discontinuation.